EGFR, HER2 and HER3 dimerization patterns guide targeted inhibition in two histotypes of esophageal cancer. Issue 7 (2nd April 2014) - Fichter, Christiane Daniela; Timme, Sylvia; Braun, Julia Alexandra; Gudernatsch, Verena; Schöpflin, Anja; Bogatyreva, Lioudmilla; Geddert, Helene; Faller, Gerhard; Klimstra, David; Tang, Laura; Hauschke, Dieter; Werner, Martin; et al.
Abstract : Receptor tyrosine kinases (RTKs) are in the focus of targeted therapy for epithelial tumors. Our study addressed the role of EGFR, HER2 and HER3 expression and dimerization in esophageal cancers in situ and in vitro in the context of therapeutic EGFR and HER2 inhibitors. In archival pretreatment biopsies of esophageal carcinomas ( n = 110), EGFR was preferentially expressed in esophageal squamous cell carcinomas (ESCCs) (22.4%; p = 0.088) and HER2 (34.4%; p < 0.001) with HER3 (91.5%; p < 0.001) in esophageal (Barrett's) adenocarcinomas (EACs). In situ proximity ligation assays revealed mainly EGFR and HER2 homodimers in ESCC and EAC cases, respectively. However, EAC cases also exhibited HER2/HER3 heterodimers. In vitro ESCC (OE21) cells displayed a significant response to erlotinib, gefitinib and lapatinib, with loss of AKT phosphorylation, G0/G1 cell cycle arrest and induction of apoptosis. In EAC cells (OE19, OE33 and SK‐GT‐4), lapatinib was similarly effective in strongly HER2‐positive (mainly HER2 homodimers and some HER2/EGFR heterodimers) OE19 and OE33 cells. The HER2‐targeting antibodies (trastuzumab and pertuzumab) given alone were largely ineffective in ESCC and EAC cells. However, both antibodies significantly induced antibody‐dependent cellular cytotoxicity in EAC (OE19 and OE33) cells upon co‐culture with peripheral blood mononuclear cells. The study reveals that overexpression of EGFR and HER2 predominantly results in homodimers in ESCCs and EACs, respectively. Still, some EACs also show HER2 dimerization plasticity, e.g ., with HER3. Such RTK dimerization patterns affect responses to EGFR and HER2 targeting inhibitors in ESCC and EAC cells in vitro and hence may influence future prediction for particularly HER2‐targeting inhibitors in EACs. Abstract : What's New? Receptor tyrosine kinases (RTKs) of the EGFR family represent valuable therapeutic targets for esophageal squamous cell carcinomas (ESCCs) and/or esophageal adenocarcinomas (EACs). However, there is a lack of studies investigating the cellular mechanisms of action of RTK inhibitors. This study reveals for the first time dimerization of EGFR, HER2 and HER3 in ESCC and EAC in vitro and in situ . EGFR and HER2 overexpression predominantly results in homodimers in ESCCs and EACs, respectively. HER3 is highly expressed in EACs, where it dimerizes with HER2. This suggests previously unconsidered mechanisms of action and may inform response prediction of HER2‐targeting inhibitors in EACs.